Competition, conflict, and compromise: Three discourses used by irrigators in England and their implications for the co-management of water resources - Whaley, Luke; Weatherhead, E. K. (Water Alternatives Association, 2015)
In this paper we use discourse analysis to explore the current dynamic that exists among farmer irrigators in England, and between irrigators and water managers in order to understand the potential for co-management to develop. To do this we employ two concepts from the field of critical discursive psychology – 'interpretive repertoires' and 'subject positions' – and apply them to a qualitative analysis of 20 interviews with farmers who are members of irrigator groups and two focus group discussions with farmers thinking about forming an irrigator group. The findings reveal that the participants drew upon three interpretive repertoires when talking about the relationship between farming and water resources management, namely the 'competition', 'conflict', and 'compromise' repertoires, with the latter being the least dominant. We situate the repertoires in their wider historical context to reveal the ideological forces at play, and conclude that the relative dominance of the competition and conflict repertoires serve as a barrier to co-management. In particular, this is because they engender low levels of trust and reinforce a power dynamic that favours individualism and opposition. At the same time, the less-dominant compromise repertoire challenges the power of the other two, providing some hope of achieving more participatory forms of water resources management in the future. To this end, we discuss how the restructuring of current agri-environment schemes and government water programmes may be used to promote the adoption and institutionalisation of the compromise repertoire in order to facilitate the emergence of co-management.
Keywords: Water resources; co-management; farming; discourse; power; England